Controversy of Early Marriage Between Religious Doctrine and Customs in Minority Areas in Indonesia - Huzaimah, Arne; Abdillah, Muhammad; Tamudin, M.; Holijah, Holijah; Rohmawati, Rohmawati; Sari, Intan Permata (IAIN Manado, 2024)
The early marriage controversy is a significant issue that affects people's views regarding marriage within the framework of Islamic religious doctrine and customs in Indonesia. This article examines how Islamic law adapts in response to socio-cultural changes, especially in regions with Muslim minority populations, which have mixed interpretations of the age of marriage. This study uses a qualitative descriptive approach with data collection through news and literature relevant to the keyword